Daily field checking list by Walter Rosene, January 15, 1933 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated January 15, 1933. This checklist was used by Walter Rosene to record birds sighted around Beaver Creek with Bob Walker and Syd between 10:15 and 12:15. Plustek--flatbed